Inside Cover: Photoinduced Formation of an Azobenzene‐Based CD‐Active Supramolecular Cyclic Dimer (Chem. Eur. J. 18/2015). Issue 18 (27th April 2015) - Sogawa, Hiromitsu; Terada, Kayo; Miyagi, Yu; Shiotsuki, Masashi; Inai, Yoshihito; Masuda, Toshio; Sanda, Fumio
<x xml:space="preserve">Abstract</x> Optically active azobenzenedicarboxylic acid derivatives were synthesized from various amino acids. They reversibly isomerize between trans and cis forms upon irradiation with UV and visible light. The trans isomers are circular dichroism (CD) silent, whereas the cis isomers are CD active due to the formation of chiral supramolecular assemblies based on the bent structures of the cis‐azobenzene moieties and hydrogen bonding between the carboxy groups. For more details, see the Full Paper by F. Sanda and co‐workers on page 6747 ff.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>